Farm characteristics and farmer perceptions associated with bovine tuberculosis incidents in areas of emerging endemic spread - Broughan, J; Maye, D; Carmody, P; Brunton, L; Ashton, A; Wint, G; Alexander, N; Enticott, G (Elsevier, 2016)
While much is known about the risk factors for bovine tuberculosis (bTB) in herds located in high incidence areas, the drivers of bTB spread in areas of emerging endemicity are less well established. Epidemiological analysis and intensive social research identified natural and social risk factors that may prevent or encourage the spread of disease. These were investigated using a case–control study design to survey farmers in areas defined as recently having become endemic for bTB (from or after 2006). Telephone surveys were conducted for 113 farms with a recent history of a bTB incident where their officially tuberculosis free status had been withdrawn (OTFW) (cases) and 224 controls with no history of a bTB incident, matched on location, production type and the rate of endemic bTB spread. Farmers were questioned about a range of farm management strategies, farm characteristics, herd health, wildlife and biosecurity measures with a focus on farmer attitudes and behaviours such as farmers’ perception of endemicity and feelings of control, openness and social cohesion. Data generated in the telephone surveys was supplemented with existing herd-level data and analysed using conditional logistic regression. Overall, herd size (OR 1.07), purchasing an animal at a cattle market compared to purchasing outside of markets (OR 2.6), the number of contiguous bTB incidents (2.30) and the number of inconclusive reactors detected in the 2 years prior to the case incident (OR 1.95) significantly increased the odds of a bTB incident. Beef herds using a field parcel more than 3.2 km away from the main farm and dairy herds reporting Johne’s disease in the previous 12 months were 3.0 and 4.7 times more likely to have a recent history of a bTB incident, respectively. Beef herds reporting maize growing near, but not on, their farm were less likely to be case herds. Operating a closed farm in the two years prior to the case breakdown did not reduce the odds of a bTB incident. Farmers that had recently experienced a bTB incident were more likely to have implemented badger biosecurity in the previous year, but no more likely than control farms to have implemented cattle biosecurity. Case farmers felt significantly less likely to be influenced by government, vets or other farmers compared to those with no history of bTB. This suggests that alternative methods of engaging with farmers who have recently had a breakdown may need to be developed.